Numerical analysis of blast pressure parameters on human with and without wall as a barrier - Nurul Aina, Marudin (2019)
Blast is the pressure over and above normal atmospheric pressure caused by a shock wave. In today's era, studying the impact of blast load on human has become important due to the increase in cases of human injury and fatality caused by events of explosion. The blast pressure will affect the surrounding area will definitely cause human injury and fatality. Barrier walls can be built as one of the effective approaches from possible explosion events to ensure human safety. Further investigation on the impact of blast load on the barrier is needed to provide an ideal structural design as the barrier. In this thesis, the aim of this study is to investigate blast overpressure of l3.6lkg which is equivalent to 30 lbs. Trinitrotoluene (TNT) to a wall and its surrounding and to study the effect on blast pressure subjected to human with and without wall as a barrier. This study is focusing on the numerical analysis between two cases involved as possible situations which are; Case 1- numerical analysis of blast pressure parameters on human without wall, and Case 2- numerical analysis of blast pressure parameters on human with wall as a barrier. The acquired blast parameters from numerical results are compared with blast test where AUTODYN non-linear finite element (FE) analysis commercial software is used to develop a validated numerical model against published experimental result such as recorded blast pressure data. This research appraises the possible blast pressure produced by blast load of 30lbs TNT on human at selected location. Thus, research outcome for this study is to determine the effect of blast pressure on human will cause any casualty or fatality. The existing knowledge of predicted blast pressure numerically has been embraced in this paper for detail understanding. The numerical result obtained at different position on the structure are also presented and compared. The result analysis shows that blast pressure is reduced when there is a wall as barrier compared to when there is no presence of wall. In addition, the result as presented in pressure-time graph shows that blast pressure behaves in decreasing manner against increasing time and distance. As in the numerical analysis, it resulted with the highest peak in blast pressure parameter in free field (Case I) is 690 kPa which the impact on human is prone to possible I 00% fatality approach and the injury is from rupture eardrum and damaged lungs. While the minimum peak pressure in Case l is 125 kPa which have the effect of possible most people are killed and the possible injury is 50% chance of eardrum rupture and possible damaged lungs. Whereas the highest peak pressure in case 2 is 256 kPa which has the effects based on literature review concluded as slight chance of severe lung damage, possible rupture eardrum, and approach I 00% fatalities. For the minimum peak of 125 kPa in case 2 is resulted with similar effect to minimum peak pressure in case I. The results obtained from this study can be used to assist in future study on blast pressure parameters on human.